Successfully salvaging a HIV-positive patient with mixed CIDP and meningoencephalitis: a case report - Wang, Wen; Yang, Jun; Liu, Xinchao; Wen, Ying (Frontiers in Medicine, 2025)
We describe an acquired immunodeficiency syndrome (AIDS) patient who first exhibited chronic inflammatory demyelinating polyneuropathy (CIDP) and subsequently developed meningoencephalitis due to ganciclovir (GCV)-resistant cytomegalovirus (CMV) infection. The patient first presented with peripheral nervous system (PNS) symptoms, followed by central nervous system (CNS) symptoms. Based on auxiliary examinations, including cerebrospinal fluid (CSF) tests, electromyography (EMG), brain magnetic resonance imaging (MRI) and GCV drug resistance tests, the patient was diagnosed with CIDP and meningoencephalitis due to CSF GCV-resistant CMV. After the combined application of intravenous immunoglobulin treatment, corticosteroid treatment, antiretroviral therapy (ART), and adjusted anti-CMV treatment, the patient achieved persistent relief. This case underscores the importance of considering CMV as a common etiology of neurological disorders in AIDS patients. It also highlights the necessity of prompt drug resistance testing when anti-CMV therapy yields suboptimal responses.